2008
DOI: 10.1111/j.1365-2230.2008.02730.x
|View full text |Cite
|
Sign up to set email alerts
|

Widespread granuloma annulare and Hodgkin's disease

Abstract: The presence of coexistent disseminated granuloma annulare (GA) and Hodgkin's disease (HD) is rare, with only six reported patients to date. We describe a patient with HD who had limited GA 2 years before the diagnosis of HD; widespread GA appeared after first-line treatment and heralded disease relapse. GA lesions showed hypermetabolic images on positron emission tomography, an interesting finding of unknown significance. We suggest a new pathophysiological mechanism for this association, i.e. that the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 11 publications
1
16
0
2
Order By: Relevance
“…It has been suggested that GA arises from an immunological reaction to an unidentified antigen 6. In delayed-type hypersensitivity reactions, Th1 cells secrete IFN-γ and macrophage inhibitory factor, leading to monocyte accumulation and degradation of connective tissue by lysosomal enzymes 2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that GA arises from an immunological reaction to an unidentified antigen 6. In delayed-type hypersensitivity reactions, Th1 cells secrete IFN-γ and macrophage inhibitory factor, leading to monocyte accumulation and degradation of connective tissue by lysosomal enzymes 2.…”
Section: Discussionmentioning
confidence: 99%
“…Hematologic malignancies are the most frequently reported. Both Hodgkin [49][50][51][52][53][54] and non-Hodgkin 49,55-57 lymphoma and leukemias [58][59][60][61] have been reported in patients with GA. Solid tumors have also been reported, however, in association with GA.…”
Section: Systemic Associationsmentioning
confidence: 99%
“…The coexistent neoplasms included carcinomas, lymphomas, and acute myeloid leukemia, while separate manuscripts described additional cases of GA in patients with schwannoma, [12] visceral malignancy, [13] Hodgkin disease, [14] and chronic myelomonocytic leukemia. [15] While Li et al [11] found no definite relationship between GA and malignancy, they suggest the investigation of underlying malignancies particularly for older patients with skin lesions that histologically, but not necessarily clinically, resemble GA.…”
Section: Is Granuloma Annulare Associated With Hematopoietic and Solimentioning
confidence: 99%